DAMPAK KEBIJAKAN INTERNATIONAL TRIPARTITE RUBBER COUNCIL DALAM MEMBATASI KUOTA EKSPOR KARET ALAM TERHADAP INDONESIA - Andresta Welatama; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explain about Impact of International Tripartite Rubber Council policy in limiting rubber export quota to Indonesian economy limiting export quotas and rubber production during October 2012 until March 2013. The implementation of quota restrictions aims to increase the price of natural rubber that has dropped dramatically since December 2010.In this research the authors use the perspective of pluralism. International Relations is a study of the interaction between several actors participating in international politics that include countries, international organizations, non-governmental organizations, sub-national entities such as bureaucracy and the domestic government as well as individuals. Given the pluralist perspective that has been put forward, the level of analysis used by the author is the level of group behavior analysis. In this study the authors use the theory of international organizations. International organizations in the economic field that can be defined as a sustainable formal structure whose formation is based on agreements between its members (government and non-government) from two or more sovereign states with the aim of achieving the common goals of its members. It can be concluded from this research that the impact of International Tripartite Rubber Council's is not able to increase long-term rubber price, rubber price can only increase when the policy is running because of low demand of export destination country.Keywords : ITRC (International Tripartite Rubber Council), Natural Rubber, Quota restrictions, Increase the price of rubber